Bridging Identities, Weaving Words: Exploring the Complex Tapestry of Learner Identity in Blended Learning through Collaborative Writing - Moh Ruzin; Nanang Zubaidi (Universitas Cokroaminoto Palopo, 2025)
In blended learning environments, learner identity construction and the factors influencing it have received less attention than the extensive study on language learner identity in face-to-face classroom settings. This critical review paper critically summarizes and reviews a qualitative case study on learner identity construction in blended learning environments through collaborative writing presented in Chen et al.’s (2022) study. Their research addresses a significant gap in second language acquisition by exploring identity construction across online and offline contexts. Through class observations, recordings, platform logs, and interviews, the researchers identified distinct learner identities in face-to-face sessions (Group Leader, Spokesperson, Summarizer, and Follower) and online writing (Industrious Contributor, Prudent Reader, Procrastinator, and Cooperative Writer). The study reveals that identity construction stems from interactions between personal factors (language proficiency, personality traits) and contextual elements (peer dynamics, assigned roles, teacher supervision). In this critical review paper, the researchers analyse the study's methodological approach, findings, and theoretical contributions, highlighting strengths (comprehensive exploration, data triangulation) and limitations (small sample size, lack of demographic diversity). Chen et al.'s study contributes valuable insights into the dynamic nature of learner identity in contemporary educational settings and offers practical implications for curriculum design in blended environments.